(untitled) (Ameghiniana, 2014)
A new record (Galea tixiensis n. sp.) and the anatomy of Galea from the archaeological sites Cueva Tixi and Cueva El Abra, Buenos Aires province are described herein. The bearing levels were radiometrically dated (C14). Individuals of this species may reach a larger size than other known species of the genus, reaching a similar size to that of Cavia aperea Erxleben. This new species is characterized by a greater development of the interpremaxilar foramen, the rhomboid incisive foramen, wide palate, and robust zigomatic arch. This species became extinct during historical times.